STUDI KOMPARASI PRESTASI BELAJAR BIOLOGI ANTARA METODE RESITASI DENGAN MODUL DAN METODE CERAMAH PADA SUB KONSEP REPRODUKSI TUMBUHAN DAN PEMENCARANNYA - DWI OETOMO; SUMANTO SUMANTO; PURWANTI PURWANTI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2005)
The goal of this research was to compare the recitation method using the module and talkative method. Those two methods were applied on the course on the topics of plant reproduction and its dispersal.This was the experimental research which held in SMA N 2 Sukoharjo. Documentation and test method were used in this research which was sampled clustered and randomically. The data obtain was then analyzedby t test.The conclusion was that the recitation method was better than talkative method. That conclusion based on the statistical data observed (tM > ttab = 3, 66 > 1, 66 at the significance level of 5%).